Damp Diagnosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
A simplified pediatric school entry screening examination for the syndrome of deficits in attention, motor control and perception (DAMP) is suggested from the Goteborg University, Sweden.